The Implementation of The Cambridge Curriculum in Indonesian EFL Contexts: A Systematic Literature Review - Dzakiyatun Naqia; Dini Fitriani; Fadilla Oktaviana (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2026)
This systematic literature review examines the application of the Cambridge curriculum in the context of English as a Foreign Language (EFL) in Indonesia and discusses how to integrate international educational frameworks with local systems to enhance language proficiency and global competencies. Referencing Communicative Language Teaching (CLT) and the 2018-2025 Curriculum Adaptation Theory, this study integrates empirical and theoretical insights to identify processes, challenges, benefits, and outcomes. Using the PRISMA 2020 model, a qualitative systematic review was conducted via PubMed, ScienceDirect, Mendeley, and ResearchGate. After scrutinizing 85 records using keywords such as “Implementation” AND “Cambridge Curriculum” and “Cambridge Curriculum” AND “Indonesian EFL,” 10 studies were extracted. The findings reveal that learner-centered educational strategies, such as project-based learning and the use of digital tools, promote student engagement, confidence, and critical thinking. While particularly evident in private and Islamic schools, challenges exist, including resource constraints, the need for teacher training, and cultural mismatches. The discussion relates this to theoretical frameworks, emphasizing the importance of contextualizing national curricula (such as Merdeka) and effective hybrid models. In conclusion, the Cambridge curriculum holds significant potential to advance EFL education in Indonesia through adaptive implementation. Policy makers are recommended to prioritize professional development and ensure equitable resource allocation to optimize learner outcomes across diverse settings.